Von der Notwendigkeit der Verknüpfung von National- und Fremdsprachen im Prozess der Alphabetisierung und der informellen Bildung in Burkina Faso - Bationo, Jean-Claude (Stellenbosch Papers in Linguistics Plus, 2012)
According to the 2006 national census 71,06% of Burkina Faso’s estimated 14 million inhabitants arefunctionally illiterate. This staggering number is referred to in explaining the slow social, economicaland political development of the country; it is also linked to the high incidence of poverty in BurkinaFaso. The government is aware of these connections between literacy and social circumstances andthus is determined to combat poverty through a literacy campaign. This article describes some of theseattempts and critically reflects on the importance of the mastery of literacy in national languages,linking this also to the teaching and learning of foreign languages.Keywords Schlüsselbegriffe: .Alphabetisierung, informelle Bildung, Sprachenpolitik, Nationalsprachen undFremdsprachen, Stellensuche: literacy, informal education, language policy, national languages, foreign languages,employment